Preparative separation of phytosterol analogues from green alga Chlorella vulgaris using recycling counter‐current chromatography. Issue 11 (4th May 2017) - Wu, Jianbing; Liu, Chunping; Lu, Yanbin
Abstract : The unicellular alga Chlorella vulgaris is a well‐known health food. It has been proven that the minor phytosterols, ergosterol and its analogue, are an important class of bioactive substances in C. vulgaris . In this work, a recycling counter‐current chromatographic approach was proposed for preparative separation of two analogue sterols from crude extract of C. vulgaris . The separation unit was set up with a type‐ J instrument coupled with a column switching valve. A two‐phase solvent system composed of n ‐hexane/dichloromethane/acetonitrile (10:3:7, v/v/v) was selected and optimized. After five cycles of separation, two analogue sterols were baseline separated, producing 11.7 mg 26‐nor‐25‐isopropyl‐5, 7, 22‐trien‐3β‐ol and 20.3 mg ergosterol from 300 mg of C. vulgaris extract. Their purities were both above 95%. The structures of two sterols were identified by using NMR spectroscopy.